Advances in immunoassay‐based strategies for mycotoxin detection in food: From single‐mode immunosensors to dual‐mode immunosensors. Issue 2 (30th January 2023) - Chen, Mengting; Qileng, Aori; Liang, Hongzhi; Lei, Hongtao; Liu, Weipeng; Liu, Yingju
Abstract: Mycotoxin contamination in foods and other goods has become a broad issue owing to serious toxicity, tremendous threat to public safety, and terrible loss of resources. Herein, it is necessary to develop simple, sensitive, inexpensive, and rapid platforms for the detection of mycotoxins. Currently, the limitation of instrumental and chemical methods cannot be massively applied in practice. Immunoassays are considered one of the best candidates for toxin detection due to their simplicity, rapidness, and cost‐effectiveness. Especially, the field of dual‐mode immunosensors and corresponding assays is rapidly developing as an advanced and intersected technology. So, this review summarized the types and detection principles of single‐mode immunosensors including optical and electrical immunosensors in recent years, then focused on developing dual‐mode immunosensors including integrated immunosensors and combined immunosensors to detect mycotoxins, as well as the combination of dual‐mode immunosensors with a portable device for point‐of‐care test. The remaining challenges were discussed with the aim of stimulating future development of dual‐mode immunosensors to accelerate the transformation of scientific laboratory technologies into easy‐to‐operate and rapid detection platforms.